Biogenesis and secretion of exosomes - Kowal, Joanna; Tkach, Mercedes; Théry, Clotilde (Current opinion in cell biology, 2014)
•ESCRT proteins, lipids and tetraspanins can independently generate intraluminal vesicles.•Different RAB proteins can target multivesicular compartments to the plasma membrane.•Vesicles with different densities, and probably different origins, are co-secreted. Although observed for several decades, the release of membrane-enclosed vesicles by cells into their surrounding environment has been the subject of increasing interest in the past few years, which led to the creation, in 2012, of a scientific society dedicated to the subject: the International Society for Extracellular Vesicles. Convincing evidence that vesicles allow exchange of complex information fuelled this rise in interest. But it has also become clear that different types of secreted vesicles co-exist, with different intracellular origins and modes of formation, and thus probably different compositions and functions. Exosomes are one sub-type of secreted vesicles. They form inside eukaryotic cells in multivesicular compartments, and are secreted when these compartments fuse with the plasma membrane. Interestingly, different families of molecules have been shown to allow intracellular formation of exosomes and their subsequent secretion, which suggests that even among exosomes different sub-types exist.